Mental health and psychological well-being among professional rugby league players from the UK. Issue 1 (24th February 2020) - Nicholls, Adam Robert; Madigan, Daniel J; Fairs, Lucas R W; Bailey, Richard
Abstract : Objective: This study aimed to measure depressive symptoms, anxiety symptoms and psychological well-being among a sample of Super League players, the highest tier of professional rugby league in the northern hemisphere. Methods: Between November 2018 and July 2019, a sample of 233 Super League players completed questionnaires that assessed depressive symptoms, anxiety symptoms and psychological well-being. Results: Players exhibited normal (85.8%), mild (11.6%) or moderate/severe (2.6%) depressive symptoms. Additionally, players reported normal (67.4%), mild (18.9%) or moderate/severe (13.7%) anxiety symptoms. The mean psychological well-being score across the sample was 25.07 (SD=4.34). 35.2% of players scored below average for this construct. Conclusion: The prevalence of mild depressive symptoms, moderate/severe depressive symptoms and mild anxiety symptoms among Super League players preliminary appear higher than in the general population from the UK. Much more research is needed to understand mental health among elite athletes.